Empatia e senso storico - Bondì, Roberto (Bollettino Filosofico, 2022)
What is the relationship between empathy and historical sense? Can we speak, also with regard to historical thinking, of an unnatural nature? What does it mean to understand the past? Does empathic understanding necessarily entail the renunciation of one’s own identity? And is it really always possible to understand empathically? These are the questions this essay attempts to answer in some way. Keywords: Empathy, Historical Sense, Historical Thinking, Past, the Familiar and the Strange